A systematic review of the research progress of non-coding RNA in neuroinflammation and immune regulation in cerebral infarction/ischemia-reperfusion injury - Yang, Kailin; Zeng, Liuting; Ge, Anqi; Wang, Shanshan; Zeng, Jinsong; Yuan, Xiao; Mei, Zhigang; Wang, Guozuo; Ge, Jinwen (Frontiers in Immunology, 2022)
Cerebral infarction/ischemia-reperfusion injury is currently the disease with the highest mortality and disability rate of cardiovascular disease. Current studies have shown that nerve cells die of ischemia several hours after ischemic stroke, which activates the innate immune response in the brain, promotes the production of neurotoxic substances such as inflammatory cytokines, chemokines, reactive oxygen species and nitrogen oxide, and mediates the destruction of blood-brain barrier and the occurrence of a series of inflammatory cascade reactions. Meanwhile, the expression of adhesion molecules in cerebral vascular endothelial cells increased, and immune inflammatory cells such as polymorphonuclear neutrophils, lymphocytes and mononuclear macrophages passed through vascular endothelial cells and entered the brain tissue. These cells recognize antigens exposed by the central nervous system in the brain, activate adaptive immune responses, and further mediate secondary neuronal damage, aggravating neurological deficits. In order to reduce the above-mentioned damage, the body induces peripheral immunosuppressive responses through negative feedback, which increases the incidence of post-stroke infection. This process is accompanied by changes in the immune status of the ischemic brain tissue in local and systemic systems. A growing number of studies implicate noncoding RNAs (ncRNAs) as novel epigenetic regulatory elements in the dysfunction of various cell subsets in the neurovascular unit after cerebral infarction/ischemia-reperfusion injury. In particular, recent studies have revealed advances in ncRNA biology that greatly expand the understanding of epigenetic regulation of immune responses and inflammation after cerebral infarction/ischemia-reperfusion injury. Identification of aberrant expression patterns and associated biological effects of ncRNAs in patients revealed their potential as novel biomarkers and therapeutic targets for cerebral infarction/ischemia-reperfusion injury. Therefore, this review systematically presents recent studies on the involvement of ncRNAs in cerebral infarction/ischemia-reperfusion injury and neuroimmune inflammatory cascades, and elucidates the functions and mechanisms of cerebral infarction/ischemia-reperfusion-related ncRNAs, providing new opportunities for the discovery of disease biomarkers and targeted therapy. Furthermore, this review introduces clustered regularly interspaced short palindromic repeats (CRISPR)-Display as a possible transformative tool for studying lncRNAs. In the future, ncRNA is expected to be used as a target for diagnosing cerebral infarction/ischemia-reperfusion injury, judging its prognosis and treatment, thereby significantly improving the prognosis of patients